School–Parent Collaboration Management in Supporting Learning Effectiveness in the Digital Era at SDN 2 Pancawarna - Karlina; Nila Kesumawati; Dessy Wardiah (Graduate Program Magister Manajemen Pendidikan, 2026)
This study aimed to describe the management of school–parent collaboration in supporting learning effectiveness in the digital era at SDN 2 Pancawarna, identify the supporting and inhibiting factors, and analyze its impact on students’ learning effectiveness. The study employed a qualitative approach using a descriptive method. Data were collected through observations, interviews, and documentation involving the principal, teachers, parents, and students as research informants. Data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that school–parent collaboration was implemented through the management functions of planning, implementation, and supervision. Collaboration activities were carried out through parenting programs, regular communication, and the utilization of digital media, particularly WhatsApp, as a communication platform between teachers and parents. Supporting factors included parental trust, commitment, active involvement, and concern for children's education. Meanwhile, inhibiting factors consisted of differences in understanding, limited parental time, low digital literacy among some parents, and unequal access to technology. The implementation of collaboration had a positive impact on learning effectiveness, as reflected in improved student discipline, learning participation, responsibility, and continuity between school-based and home-based learning. The study concludes that strengthening systematic and sustainable school–parent collaboration management is essential for enhancing learning effectiveness in the digital era.